Social Interactions and Long-Term Relationships Among Canadian Parents With Autism Spectrum Disorder: A Qualitative Study - Parisa Ghanouni; Max Trottier-Chi (Mental Illness)
Conclusions: This study is one of the first studies that highlight the perspectives of individuals on the spectrum as parents in interpersonal interactions with their children and friends. Findings from this study provide a basis for future studies to better support adults with ASD in their relationships.